Impact of structure on team performance - Acevedo González, Catherine; Rodriguez Lopez, Maria Fernanda; Bohorquez Arevalo, Luz Esperanza (Ingeniería Solidaria, 2021)
Introduction: This article is product of research on business self-organization developed at the Universidad Distrital Francisco Jose de Caldas on 2019-2020 starting from that collective intelligence (CI) has been viewed as an approach that enables from the use of the interactions among the agents and between these and the environment to increase the intelligence of the system; understood as the ability to take full advantage of distributed resources and to adapt nimbly to the changing conditions of the environmentMethodology: in the first part, the conditions that may facilitate CI are explored through a review of the literature. In the second part an experiment is designed in a micro-world environment in which incorporate some of the conditions identified to facilitate the CI in the structure of a team and its performance is compared with a team that has a hierarchical structure.Results: the teams that have a structure with facilitates CI, present on average greater performance, coordination effectiveness and adaptability, as well as better interaction dynamics among the members. These teams present higher levels of interaction, information flows and activity among the participants, reflected in the number of interventions and in the use of the resources offered in the game.Conclusions: the increase in complexity that the application of IC inducers gives the team could be a predictor of better performances in environments of increasing complexity; in contrast to teams that have structures that reduce their complexity as the hierarchical structure.Originality: This article provides evidence regarding the incidence of roles in the performance of the company.Limitations: one of the main constraints is the virtual interaction between the participants and between them with the research team. Face-to-face interaction would allow more intensive use of affiliate links between participants.